Safety and effectiveness of electronic cigarettes: a narrative review - ., Aziz-ur-Rahman; Nik Mohamed, Mohamad Haniki; Jamshed, Shazia Qasim (Japan International Cultural Exchange Foundation (JICEF), 2015)
Objective: To current review the literature regarding safety and effectiveness of electronic cigarettes and to find out any con- tribution from Malaysia, regarding electronic cigarettes research field. Design: To commendably face this new challenge, health care providers need to become more familiar with the existing liter- ature. A narrative review studies conducted from 2004 to August 2014 through multiple electronic databases that available at the author's institution library conducted by using the terms, safety, effectiveness, efficacy, chemical analysis of e-cigs, electron- ic cigarettes or electronic nicotine delivery system (ENDS). The databases searched only for full text papers published in English from 2004 to august 2014. Methods: 48 original articles identified with help of multiple electronic databanks, that linked to aim title were selected. Nation wise contribution included, USA(16), UK(07), Italy(6), Greece(5), New Zealand(5), Switzerland(4), Canada, Australia, Poland, south Korean, Czech republic each 1. We did not found any article from Malaysia, this indicate us there is a necessity of electronic cigarettes studies on Malaysian population. Conclusion: Due to limited studies with inadequate participants and short time exposure in some developed countries, e-cig cannot accomplish safe and effective in complete terms. In order to conclude firmly, still more research is needed globally in dif- ferent population to look at its long-term safety and effectiveness particularly on cardiovascular diseases and on smoker’s health from different parts of the world.